Trends of polypharmacy among older people in Asia, Australia and the United Kingdom: a multinational population-based study. (21st February 2023) - Lee, Hyesung; Baek, Yeon-Hee; Kim, Ju Hwan; Liao, Tzu-Chi; Lau, Wallis C Y; Man, Kenneth K C; Qin, Xiwen; Wood, Stephen; Ilomäki, Jenni; Bell, J Simon; Lai, Edward Chia-Cheng; Leung, Miriam T Y; et al.
Abstract: Background: Polypharmacy among older people represents a global challenge due to its association with adverse drug events. The reported prevalence of polypharmacy varies widely across countries, and is particularly high in Asian countries. However, there is no multinational study using standardised measurements exploring variations in prescribing trends. Objective: To compare polypharmacy trends in older people in Asia, Australia and the United Kingdom. Design: Multinational, retrospective, time-trend, observational study using a common study protocol. Setting: Outpatient and community settings. Subjects: All individuals aged ≥ 65 years between 2013 and 2016. Methods: We defined polypharmacy as the concomitant use of ≥5 medications for ≥45 days per year. We estimated the annual prevalence of polypharmacy and calculated average annual percentage change (AAPC) to assess the time trends. Results: A total of 1.62 million individuals were included in this study. The highest prevalence of polypharmacy was observed in Hong Kong (46.4%), followed by Taiwan (38.8%), South Korea (32.0%), the United Kingdom (23.5%) and Australia (20.1%) in 2016. For the time trend, the Asian region showed a steady increase, particularly in Hong Kong and South Korea (AAPC: Hong Kong, 2.7%; South Korea, 1.8%; Taiwan, 1.0%). However, Australia and the United Kingdom showed a decreasing trend (Australia, −4.9%; the United Kingdom, −1.1%). Conclusions: Polypharmacy prevalence in older people was higher in Hong Kong, Taiwan and South Korea, with an increasing trend over time, compared with Australia and the United Kingdom. Our findings underline the necessity to monitor polypharmacy among older people in Asia by conducting government-level interventions and introducing medicine-optimisation strategies.